The Strategy For Increasing The Number Of Customers At Karomah Chicken Fast Food Restaurant Air Muring North Bengkulu - Weni Wulandari; Tito Irwanto; Tri Febrina Melinda (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The implementation of a strategy to increase the number of customers in a company is very influential in the performance of the company. The success or failure of a company is largely determined by the way the company has developed to be able to compete for consumers in implementing an effective marketing strategy. The purpose of this research is to increase the number of customers at Karomah Chicken in Air Muring North Bengkulu through the strengths, weaknesses, opportunities and threats that will occur in the future in increasing the number of customers. This research uses the SWOT analysis method by selecting consumers who come as respondents in this study, the number of respondents is as many as 57 people. 7 internal factors or employees at Karomah Chicken Air Muring North Bengkulu and 50 External Factors namely consumers who make transactions at Karomah Chicken Air Muring North Bengkulu. Karomah Chicken Air Muring North Bengkulu will be established in 2021 which is located on Jalan Jl. City of Bani Pasar Simpang, Putri Hijau, North Bengkulu. Based on the results of the research that using SWOT analysis, it is known that Karomah Chicken, Air Muring North Bengkulu, has a strength value of 22.68, a weakness of 8.1, so that it complements IFAS so that the EFAS quadrant is sar 22.68 – 8.1 = 14.50 while the opportunity value is 14. 98 and a threat of 7.06 so that the EFAS quadrant is 14.98 – 7.06 = 7.92 so it can be seen that Karomah Chicken of the North Bengkulu Air Muring at coordinates (14.77 – 9.84) in quadrant (1) which indicates marketing to increase the number of customers namely 1.) always maintain safety and comfort at Karomah Chicken Air Muring Bengkulu North Branch. 2.) the location of the store is located in a strategic place. 3.) adding menu variations to the products offered. Keywords: Strengths, Weaknesses, Opportunities, Threats.